(−)-Epigallocatechin-3-Gallate and Quercetin Inhibit Quiescin Sulfhydryl Oxidase 1 Secretion from Hepatocellular Carcinoma Cells - Lumin Yang; Yuying Fang; Yufeng He; Jinsong Zhang (Antioxidants)
Liver cancer is one of the most prevalent cancers worldwide. The first-line therapeutic drug sorafenib offers only a moderate improvement in patients’ conditions. Therefore, an approach to enhancing its therapeutic efficacy is urgently needed. It has been revealed that hepatocellular carcinoma (HCC) cells with heightened intracellular quiescin sulfhydryl oxidase 1 (QSOX1) exhibit increased sensitivity to sorafenib. QSOX1 is a secreted disulfide catalyst, and it is widely recognized that extracellular QSOX1 promotes the growth, invasion, and metastasis of cancer cells through its participation in the establishment of extracellular matrix. Inhibiting QSOX1 secretion can increase intracellular QSOX1 and decrease extracellular QSOX1. Such an approach would sensitize HCC cells to sorafenib but remains to be established. Since (−)-epigallocatechin-3-gallate (EGCG) has been demonstrated to be an effective inhibitor of α-fetal protein secretion from HCC cells, we screened QSOX1 secretion inhibition using polyphenolic compounds. We examined eight dietary polyphenols (EGCG, quercetin, fisetin, myricetin, caffeic acid, chlorogenic acid, resveratrol, and theaflavin) and found that EGCG and quercetin effectively inhibited QSOX1 secretion from human HCC cells (HepG2 or Huh7), resulting in high intracellular QSOX1 and low extracellular QSOX1. The combination of EGCG or quercetin, both of which change the cellular distribution of QSOX1, with sorafenib, which has no influence on the cellular distribution of QSOX1, exhibited multiple synergistic effects against the HCC cells, including the induction of apoptosis and inhibition of invasion and metastasis. In conclusion, our current results suggest that dietary EGCG and quercetin have the potential to be developed as adjuvants to sorafenib in the treatment of HCC by modulating the cellular distribution of QSOX1.